Samsung Galaxy Tab 10.1 for dummies / Dan Gookin - Gookin, Dan
Learn to: Navigate the Galaxy Tab and download apps, movies, and music at blazing 4G LTE speeds; Video chat and read eBooks on the bigger, better screen; E-mail, browse the web, and map directions for a trip.